The issues of using PISA in school geography classes - Hamrayeva Gulhayo (International Consortium of Education and Culture Research Studies, 2019)
This article about the importance of working pisa tests with geographic lessons for learning geography is determined by the fact that without a new pedagogic technology can not be realized the main feature of any geography, object and phenomenon, namely geographic.In addition to, this article about what is the PISA program.